2018
DOI: 10.1186/s13014-018-1059-1
|View full text |Cite
|
Sign up to set email alerts
|

Urethra-sparing stereotactic body radiotherapy for prostate cancer: how much can the rectal wall dose be reduced with or without an endorectal balloon?

Abstract: BackgroundThis is a dosimetric comparative study intended to establish appropriate low-to-intermediate dose-constraints for the rectal wall (Rwall) in the context of a randomized phase-II trial on urethra-sparing stereotactic body radiotherapy (SBRT) for prostate cancer. The effect of plan optimization on low-to-intermediate Rwall dose and the potential benefit of an endorectal balloon (ERB) are investigated.MethodsTen prostate cancer patients, simulated with and without an ERB, were planned to receive 36.25Gy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Indeed, measurements from real-time electromagnetic beacon data have shown that in the absence of intra-fractional corrections, a posterior margin of 3 mm would result in unacceptably low (93%) CTV coverage (32). If we assume 1-2 mm margins are necessary for systematic errors related to contouring and machine performance (33)(34)(35), then the minimum PTV margins required in the absence of frequent intra-fractional monitoring and correction would be 2.9-3.9 mm LR, 3.7-4.7 mm SI, and 4.1-5.1 mm AP. The fact that a greater posterior margin is necessary is practically relevant, as many contemporary SBRT protocols allow for smaller posterior margins (5,(36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, measurements from real-time electromagnetic beacon data have shown that in the absence of intra-fractional corrections, a posterior margin of 3 mm would result in unacceptably low (93%) CTV coverage (32). If we assume 1-2 mm margins are necessary for systematic errors related to contouring and machine performance (33)(34)(35), then the minimum PTV margins required in the absence of frequent intra-fractional monitoring and correction would be 2.9-3.9 mm LR, 3.7-4.7 mm SI, and 4.1-5.1 mm AP. The fact that a greater posterior margin is necessary is practically relevant, as many contemporary SBRT protocols allow for smaller posterior margins (5,(36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…The use of hydrogel spacers could serve to move the rectal wall out of the high‐dose region, meaning that the relative dose changes we observe around unplanned gas cavities would result in lower absolute dose increases. Furthermore, using an air‐ or a liquid‐filled EndoRectal Balloon (ERB) to create a planned cavity could potentially avoid large unplanned air cavities forming . Another option could be to employ a new gas‐release balloon, originally designed for proton treatment, which has been seen to reduce the frequency of trapped air …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, using an air-or a liquid-filled EndoRectal Balloon (ERB) to create a planned cavity could potentially avoid large unplanned air cavities forming. 16,[41][42][43] Another option could be to employ a new gas-release balloon, originally designed for proton treatment, which has been seen to reduce the frequency of trapped air. 44…”
Section: A Implications Of Unplanned Gas In the Rectal Wallmentioning
confidence: 99%
“…1 using a threshold limit for Calypso ® of ±3 mm with geometric check limits set to 2 mm (geometrical residual) and rotations of 10° (default values). Table 1 summarizes the dose constraints for the OAR [ 24 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%